2017
DOI: 10.1073/pnas.1711160114
|View full text |Cite
|
Sign up to set email alerts
|

A STAT3-dependent transcriptional circuitry inhibits cytotoxic gene expression in T cells

Abstract: CD8 T cells are preprogrammed for cytotoxic differentiation in the thymus as they acquire expression of the transcription factor Runx3. However, a subset of effector CD8 T cells (Tc17) produce IL-17 and fail to express cytotoxic genes. Here, we show that the transcription factors directing IL-17 production, STAT3 and RORγt, inhibit cytotoxicity despite persistent Runx3 expression. Cytotoxic gene repression did not require the transcription factor Thpok, which in CD4 T cells restrains Runx3 functions and cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…Studies in melanoma and lung cancer models have found that genetic lack of STAT3 in T cells results in increased migration and effector function (56,57). These observations, together with our data and studies showing that STAT3 regulates proliferation, survival, cytotoxic gene expression, and memory function in CD8 þ T cells that respond to viral infections, suggest that STAT3 could be a possible therapeutic target for enhancing antitumor CD8 þ T cellmediated responses (58,59). Further work needs to be done to establish if IL35 blockade and/or inhibition of STAT3 in effector T cells generates persistent memory responses and may provide further insight into strategies for combination immunotherapy.…”
Section: Discussionsupporting
confidence: 69%
“…Studies in melanoma and lung cancer models have found that genetic lack of STAT3 in T cells results in increased migration and effector function (56,57). These observations, together with our data and studies showing that STAT3 regulates proliferation, survival, cytotoxic gene expression, and memory function in CD8 þ T cells that respond to viral infections, suggest that STAT3 could be a possible therapeutic target for enhancing antitumor CD8 þ T cellmediated responses (58,59). Further work needs to be done to establish if IL35 blockade and/or inhibition of STAT3 in effector T cells generates persistent memory responses and may provide further insight into strategies for combination immunotherapy.…”
Section: Discussionsupporting
confidence: 69%
“…The acquisition of cytotoxic functions by Tfh cells would be deleterious as it would result in the destruction of GC B cells. We found that in the absence of Thpok, Bcl6 failed to inhibit the expression of cytotoxic genes, unlike other ''master'' regulators of CD4 + T cell fates, including Gata3 and Stat3 (Ciucci et al, 2017;Yagi et al, 2010). This is consistent with Bcl6 being expressed in CD8 + T cells and contributing to the differentiation of memory CD8 + T cells (D'Cruz et al, 2009;Wu et al, 2016), and it reinforces the importance of Thpok inhibition of cytotoxic genes for the GC reaction.…”
Section: Discussionsupporting
confidence: 79%
“…However, both population and single-cell RNA-seq analyses showed that Thpok was not needed for CD4 + T cells to adopt key marks of the Th1 transcriptome, supporting the idea of a specific impact of Thpok on Tfh differentiation during responses to intracellular pathogens. In line with the concept of fate-specific effects of Thpok, we and others previously reported that Thpok is not necessary for Th17 cell differentiation (Ciucci et al, 2017;Reis et al, 2013;Vacchio et al, 2014). In addition, the mechanistic impact of Thpok deletion on effector differentia-tion is lineage specific, as it is mediated by the repression of Runx3 during Th2 cell differentiation (Vacchio et al, 2014) and the expression of Bcl6 during Tfh cell differentiation.…”
Section: Discussionsupporting
confidence: 72%
“…In this model, human naive CD4 T cells stimulated in the presence of Th1, and not Th2 or Th17, polarizing cytokines differentiated in perforin + granzyme B + cells with potent cytotoxic activity. This could be due to the promotion of the cytotoxic phenotype by Th1 cytokines or to its repression by the Th2 or Th17 transcriptional programs, or both ( Parronchi et al, 1992 ; Xiong et al, 2013 ; Ciucci et al, 2017 ). In contrast to the rapid acquisition of IFNG expression, naive CD4 T cells expressed high levels of PRF1 1 to 2 weeks after stimulation.…”
Section: Discussionmentioning
confidence: 99%